2021
DOI: 10.1371/journal.pone.0247161
|View full text |Cite
|
Sign up to set email alerts
|

Short term visual and structural outcomes of anti-vascular endothelial growth factor (anti-VEGF) treatment delay during the first COVID-19 wave: A pilot study

Abstract: Regularly scheduled intravitreal anti-vascular endothelial growth factor (anti-VEGF) injections are essential to maintaining and/or improving many ocular conditions including: neovascular age-related macular degeneration (nAMD), diabetic retinopathy, and retinal vein occlusions with macular edema (RVO). This study aims to assess the effect of unintended delays in anti-VEGF treatment during the first wave of the COVID-19 pandemic. This retrospective case series identified patients receiving regularly scheduled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 17 publications
4
36
0
Order By: Relevance
“…General guidelines on the management of nAMD were prepared after the onset of the pandemic [13,14], recommending treatment administration for every nAMD patient every two months, regardless visual functional or macular anatomical aspects, in an empirical attempt to minimize what was expected to be a mayor disaster. It is clear that this catastrophic situation has had a negative impact on functional and anatomic outcome of nAMD, as can be seen in our cohort and also in the majority the studies published in 2021 about this subject [15][16][17][18][19][20][21][22]. Even with an average delay of one month, Borrelli et al [15] found significant loss of BCVA and proportional to visit delay.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…General guidelines on the management of nAMD were prepared after the onset of the pandemic [13,14], recommending treatment administration for every nAMD patient every two months, regardless visual functional or macular anatomical aspects, in an empirical attempt to minimize what was expected to be a mayor disaster. It is clear that this catastrophic situation has had a negative impact on functional and anatomic outcome of nAMD, as can be seen in our cohort and also in the majority the studies published in 2021 about this subject [15][16][17][18][19][20][21][22]. Even with an average delay of one month, Borrelli et al [15] found significant loss of BCVA and proportional to visit delay.…”
Section: Discussionsupporting
confidence: 67%
“…In the study by Naravane et al [16], 36 patients diagnosed with neovascular AMD experienced delays in treatment (defined as more than 14 days) and visual acuity decreased 6.2 letters (from 48.6 to 42.3, p = 0.04). In our study with 270 eyes, mean delay of 110 days meant a change of −3.6 letters.…”
Section: Discussionmentioning
confidence: 98%
“…Within the DME subgroup, patients whose injections were delayed trended towards a decline in vision from logMAR 0.544 (Snellen 20/70) pre-lockdown to logMAR 0.722 (Snellen 20/105) on follow-up (p = 0.06). In contrast, patients whose injections were not delayed did not experience a statistically significant decline in vision (p = 0.40) [31]. Delayed anti-VEGF treatment in patients with DME also resulted in an increase in mean central subfield thickness from 341 to 447 µm (p = 0.007).…”
Section: Impact Of Delayed Care On Visual Outcomesmentioning
confidence: 93%
“…Although diabetic retinopathy represents the largest subgroup of patients, there was a significant decline in the number of patients with diabetic retinopathy attending the clinic during the pandemic period. Naravane et al [22] reported that treatment delays had a negative impact on the visual and anatomic outcomes of patients with neovascular AMD and DME during the COVID-19 lockdown in Minnesota. They compared the VA and structural changes in the retina using ocular OCT and observed worse visual outcomes in the delayed treatment group [22].…”
Section: Discussionmentioning
confidence: 99%